Socialization Of Making Fermented Goat Urine Liquid Organic Fertilizer - M. Wasito; Lubis, Najla; Sulardi; Muhammad Ibnu Al Alif (International Forum of Researchers and Lecturers, 2024)
Goat urine is liquid waste from goat feces. Goat urine is able to provide macro and micro nutrients and contains growth regulators (ZPT) that plants need. Goat urine contains 1.5% nitrogen, 0.13% phosphorus, and 1.8% potassium. Goat urine contains natural hormones of IAA, gibberellin, and cytokinin higher than other livestock urine. Goat urine processing can be done by fermentation. Fermentation is a process of chemical changes in an organic substrate through enzyme activity produced by microorganisms. The results of fermentation of organic materials such as sugar, alcohol, amino acids, proteins, carbohydrates, vitamins and other organic compounds are easily absorbed directly by plant roots. The use of effective microorganisms in the manufacture of goat urine fermented liquid organic fertilizer aims to accelerate the fermentation process. Effective microorganisms or also known as probiotics are mixed cultures of various types of beneficial microorganisms such as photosynthetic bacteria, lactic acid bacteria, actinomycetes yeasts, fermentation fungi that can improve soil microbes. The use of solid waste of goat manure is commonly done by farmers, but the use of liquid waste (urine) of fermented goats has not been widely known. Therefore, it is important to optimize the use of fermented goat urine as liquid organic fertilizer.